Banking technology in Malaysia based on the interactive voice response system: A measurement of preparedness for e-commerce - Jamaludin, Zulikha; Embong, Abdullah (2000)
The objective of this paper is to provide a clear picture about the awareness among banking customers towards virtual banking, and the implementation of interactive voice response (IVR) banking technology in Malaysia. The result of this study can be used as an important reference material to the banks for the purpose of measuring customer’s preparedness towards phone banking as one of the popular method of e-commerce. The methods used for data collection were library search, questionnaires and interview. The respondents consisted of two groups: bank’s customers, and commercial banks, which implemented the IVR system. Data were analyzed using descriptive statistics. The findings highlighted the following issues: (1) customers' profile and the profile of the commercial banks implementing IVR system; (2) the benefit of the system as viewed by the customers and the banks; (3) the cost of accessing the system; (4) the channel of accessing the bank services; (5) the kind of IVR banking services offered; (6) service charges; (7) the developer of the system and the configuration/technology used; and (8) the future of IVR banking. The results revealed that the IVR banking attracted younger customers who believed that this method of banking could increase the customer service and satisfaction because the system can be accessed at any time. However, accessing the bank services via telephone is not the most popular channel of banking. The most popular services are balance inquiry and bills payments. Almost all IVR banking customers found that banking by phone is a lot cheaper, whereas non-IVR customers believe otherwise. Configuration, technology, lines support, hardware and software supports do not differ very much from one bank to another. They use a model, which is quite similar although not the same. To date, accessing the IVR banking services does not incur extra charges, except for third party bill payments. Based on the findings, the future of IVR banking in Malaysia is definitely bright, thus it is considered as a booster for e-commerce in this country.